Design of An AppSheet Based Inventory Management Information System for Warehouses Using the Waterfall Method - Jaya, Firdan Anugrah; Suherman, Amay; Rahman, Aulia Zikri (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
Accurate inventory recording is a crucial aspect of maintaining warehouse operational efficiency. XYZ Institution is a government agency that operates two distinct types of warehouses: the Central Supply Warehouse and the Environmental Chemical Warehouse. Historically, manual inventory recording in both warehouses has resulted in discrepancies between system data and actual field conditions, with an average data accuracy of only 67% in the Central Supply Warehouse and 44% in the Environmental Chemical Warehouse. This study aims to develop an inventory management application based on AppSheet using the Waterfall method, which includes the stages of design, implementation, and Black Box testing to verify the application's functionality. The application users consist of an admin, who acts as the warehouse supervisor, and end users, namely staff of the Central Supply Warehouse and the Environmental Chemical Warehouse, each with workflows tailored to their respective operational requirements. The test results indicate that the application successfully meets the designed system requirements and is ready for operational use. It is expected that the implementation of this application will serve as an initial step toward the broader digitalization of logistics systems within government institutions